2008
DOI: 10.1111/j.1538-7836.2007.02841.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin activatable fibrinolysis inhibitor is associated with severity and outcome of severe meningococcal infection in children

Abstract: To cite this article: Emonts M, de Bruijne ELE, Guimarã es AHC, Declerck PJ, Leebeek FWG, de Maat MPM, Rijken DC, Hazelzet JA, Gils A.Thrombin activatable fibrinolysis inhibitor is associated with severity and outcome of severe meningococcal infection in children. J Thromb Haemost 2008; 6: 268-76.Summary. Background and objectives: In pediatric meningococcal sepsis, an imbalance between coagulation and fibrinolysis and proinflammatory action play major roles. We hypothesized that thrombin activatable fibrinoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 38 publications
4
37
0
3
Order By: Relevance
“…Although only a few septic patients (n=25) were enrolled in the study, the activation status of TAFI could clearly differentiate septic patients from healthy controls. This result is in agreement with the results of a recent study [10] that reported a significant elevation of TAFI activation in meningococcal infection. Since decreases in total TAFI level are associated with increases of TAFI activation level, simultaneous determination of total TAFI and TAFI activation marker is required to interpret the role of TAFI in acquired hemostatic dysfunctions including sepsis.…”
supporting
confidence: 93%
“…Although only a few septic patients (n=25) were enrolled in the study, the activation status of TAFI could clearly differentiate septic patients from healthy controls. This result is in agreement with the results of a recent study [10] that reported a significant elevation of TAFI activation in meningococcal infection. Since decreases in total TAFI level are associated with increases of TAFI activation level, simultaneous determination of total TAFI and TAFI activation marker is required to interpret the role of TAFI in acquired hemostatic dysfunctions including sepsis.…”
supporting
confidence: 93%
“…Given that LPS hyporesponsiveness has also been reported in MyD88 (30), TRIF (5), TIRAP (5,8) and MD‐2 knockout mice (30), genetic variations in these or related genes might modulate disease susceptibility and/or clinical phenotype as well. In addition, it has been demonstrated that genetic variants in other components of the host immune and coagulation system such as TNF‐α (12), plasminogen activator inhibitor‐1 (PAI‐1) (22,31), thrombin activatable fibrinolysis inhibitor (TAFI) (32,33) or variants of the protein C (PC) promoter (34) can also modulate disease severity and/or outcome in meningococcal disease (also reviewed in (35)).…”
Section: Discussionmentioning
confidence: 99%
“…It was unclear whether activation or consumption or both were the cause of this decrease. In a comprehensive study evaluating TAFI activation markers on a rather large series of patients with severe meningococcal infection, Emonts et al128 demonstrated that TAFI levels were significantly decreased at admission compared to the convalescence state and were lower in patients with septic shock. More important, the levels of TAFI activation peptide (TAFI-AP) were augmented in patients with DIC as compared with those without.…”
Section: Pathogenesis Of Sepsis-associated Coagulopathy and Thrombus mentioning
confidence: 99%